INDUKSI TUNAS PADA DUA VARIETAS PISANG (Musa acuminata C.) TERHADAP LAMA PENGGELAPAN SECARA IN VITRO - Dzikrie Mary Ainipasha; Susiyanti Susiyanti; Sulastri Isminingsih; Zahratul Millah (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2024)
A sufficient supply of healthy plants must be provided to balance the rising demand for bananas. A technique that can be used for propagation is tissue culture. Environmental factors and a variety of types are factors that affect explant growth. This research aimed to determine the effect of darkening duration on the growth of two banana (Musa sp.) varieties in vitro. In this study, a Factorial Randomized Block Design was implemented, considering two elements, namely the variety of bananas and the duration of darkening. The research showed that the time of shoot emergence started at 1.83 WAP in Cavendish grand naine treatment without darkening. The type of variety treatment had a significant effect on the number of leaves, and the best variety was Cavendish grand naine. The darkening duration treatment with four weeks of darkening increased shoot height significantly. An interaction between these two factors was observed in the number of shoots, shoot height, and number of leaves.